SU-8 Based Microdevices to Study Self-Induced Chemotaxis in 3D Microenvironments - Ayuso, Jose Maria; Monge, Rosa; Llamazares, Guillermo A.; Moreno, Marco; Agirregabiria, Maria; Berganzo, Javier; Doblaré, Manuel; Ochoa, Iñaki; Fernández, Luis J. (Frontiers in Materials, 2015)
Tissues are complex three-dimensional structures in which cell behaviour is frequently guided by chemotactic signals. Although starvation and nutrient restriction induce many different chemotactic processes, the recreation of such conditions in vitro remains difficult when using standard cell culture equipment. Recently, microfluidic techniques have arisen as powerful tools to mimic such physiological conditions. In this context, microfluidic three-dimensional cell culture systems require precise control of cell/hydrogel location because samples need to be placed within a microchamber without obstruction of surrounding elements. In this article, SU-8 is studied as structural material for the fabrication of complex cell culture devices due to its good mechanical properties, low gas permeability and sensor integration capacity. In particular, this manuscript presents a SU-8 based microdevice designed to create “self-induced” medium starvation, based on the combination of nutrient restriction and natural cell metabolism. Results show a natural migratory response towards nutrient source, showing how cells adapt to their own microenvironment modifications. The presented results demonstrate the SU-8 potential for microdevice fabrication applied to cell culture.